2021
DOI: 10.3390/ijerph18179060
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Ready-to-Use Therapeutic Food in Improving the Developmental Potential and Weight of Children Aged under Five with Severe Acute Malnourishment in Pakistan: A Pretest-Posttest Study

Abstract: The objective of this study was to assess whether the standard therapy of ready-to-use therapeutic food in the treatment of uncomplicated severe acute malnutrition (SAM) is effective in improving developmental potential and weight gain in children aged under five years. A multicenter pretest-posttest study was conducted among 91 children aged under five with uncomplicated SAM in Pakistan. Study participants completed their eight weeks’ therapy of ready-to-use therapeutic food according to the World Health Orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Likewise, MUAC was also observed to have a net increase of 11.2±0.9 mm (p<0.0001). A recent study from Pakistan enrolling 91 children with SAM under the age of five years revealed that RUTF not only influenced significant weight gain among malnourished children but also improved the developmental potential of the malnourished children [ 17 ]. These findings are also consistent with what has been found in other studies conducted in Ethiopia, Pakistan, and Ghana [ 16 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, MUAC was also observed to have a net increase of 11.2±0.9 mm (p<0.0001). A recent study from Pakistan enrolling 91 children with SAM under the age of five years revealed that RUTF not only influenced significant weight gain among malnourished children but also improved the developmental potential of the malnourished children [ 17 ]. These findings are also consistent with what has been found in other studies conducted in Ethiopia, Pakistan, and Ghana [ 16 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that 81.7% of children with PCM were aged less than two years. Exposure to malnourishment in the infancy period is thought to cause a high risk of developmental delay in the later years of life as infancy and toddlerhood are known to be periods of rapid development and are influenced by socio-demographical and environmental issues [ 17 , 22 ]. For the treatment of malnourished children, community-based interventions for addressing acute malnutrition like RUTF is effective.…”
Section: Discussionmentioning
confidence: 99%
“…The OTP center of the teaching hospital Dera Ghazi Khan was selected for data collection. The selected area is underdeveloped, with substandard housing due to poverty and illiteracy, overcrowded poor socioeconomic conditions, malnutrition, and unhygienic living conditions [ 17 ]. The data were collected by the consultant pediatrician with the help of a lady health worker.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to other developing countries, Pakistan ranks among the worst in the prevalence of malnutrition among children under five years of age [5], causing high rates 2 of 14 of infant and under-five mortality rates. According to estimates by the Government of Pakistan, the infant mortality rate is 57 deaths per 1000 live births, while the under-five mortality rate is 65.2 deaths per 1000 live births.…”
Section: Introductionmentioning
confidence: 99%